2021
DOI: 10.1093/dnares/dsab011
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a genome-wide association study with transcriptomic data to predict candidate genes and favourable haplotypes influencing Brassica napus seed phytate

Abstract: Phytate is the storage form of phosphorus in angiosperm seeds and plays vitally important roles during seed development. However, in crop plants phytate decreases bioavailability of seed-sourced mineral elements for humans, livestock and poultry, and contributes to phosphate-related water pollution. However, there is little knowledge about this trait in oilseed rape (Brassica napus). Here, a panel of 505 diverse B. napus accessions was screened in a genome-wide association study (GWAS) using 3.28 × 106 single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The QTL identified by Bentsink et al 80 is not only associated with seed phytate but also with the seed P i concentration, leaf phytate, and P i concentrations. In addition, this QTL and a QTL affecting the seed phytate concentration in oilseed rape detected by Liu et al 84 were colocated in a syntenic region between Arabidopsis and oilseed rape (Figure S1). This major locus was further fine-mapped to a 99 kb region in which 13 open reading frames are located, with a vacuolar membrane ATPase subunit G1 (At3g01390) predicted as a promising candidate gene.…”
Section: Identification Of Qtls Affecting Natural Variation In the Se...mentioning
confidence: 87%
See 3 more Smart Citations
“…The QTL identified by Bentsink et al 80 is not only associated with seed phytate but also with the seed P i concentration, leaf phytate, and P i concentrations. In addition, this QTL and a QTL affecting the seed phytate concentration in oilseed rape detected by Liu et al 84 were colocated in a syntenic region between Arabidopsis and oilseed rape (Figure S1). This major locus was further fine-mapped to a 99 kb region in which 13 open reading frames are located, with a vacuolar membrane ATPase subunit G1 (At3g01390) predicted as a promising candidate gene.…”
Section: Identification Of Qtls Affecting Natural Variation In the Se...mentioning
confidence: 87%
“…In addition to traditional linkage mapping using biparental recombinant populations, GWAS has also been used to uncover the genetic basis of the seed phytate accumulation in oilseed rape and rice (Table ). , Additional QTLs within a narrower mapping interval can be detected by GWAS using natural populations that contain extensive genetic diversity and have undergone numerous recombination events under selection . In oilseed rape, Liu et al identified 31 QTLs associated with the seed phytate concentration by GWAS using a panel of 404 diverse oilseed rape accessions.…”
Section: Identification Of Qtls Affecting Natural Variation In the Se...mentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome analysis is a robust approach that helps the identification of differentially expressed genes with their expression level and regulatory mechanisms [ 48 ]. The present study identified 245 and 540 DEGs specific to HN/LN and HNCK/LNCK, respectively, while 399 DEGs were considered common DEGs for HN/LN/HNCK/LNCK-T1T2 ( Table S3 , Figure 3 B).…”
Section: Discussionmentioning
confidence: 99%